Amorphous carbon thin films by aerosol-assisted chemical vapor deposition for carbon-based solar cell applications / Nurfadzilah Ahmad - Ahmad, Nurfadzilah (Institute of Graduate Studies, UiTM, 2015)
Nitrogen doped amorphous carbon (a-C:N) was synthesized using a new custom-made Aerosol-assisted Chemical Vapor Deposition (AACVD) from camphor oil as the precursor. The a-C:N thin films have demonstrated better quality in uniformity, high conductivity, moderate and suitable ID/IG ratio from Raman analysis and optical band gap for solar cell applications. The doping process was successful as proven by the Energy Dispersive X-ray analysis (EDX) spectrum with the presence of Nitrogen (N) peak in a-C:N, and thus this AACVD has proven the suitability to undergo the doping process for nitrogen doped a-C:N. The produced thin films have demonstrated high conductivity with photoresponse effect towards the sun light which is very important in solar cell application. Transmittance spectrum of the nitrogen doped a-C:N exhibit a large transmittance value (>85%) and high absorption coefficient value of 106 cm-1 and the value was higher than undoped a-C (103-104 cm-1)…